Control of Behavioral Arousal and Defense by a Glutamatergic Midbrain-Amygdala Pathway in Mice - Chen, Shang-Yi; Yao, Jing; Hu, Yu-Duan; Chen, Hui-Yun; Liu, Pei-Chang; Wang, Wen-Feng; Zeng, Yu-Hang; Zhuang, Cong-Wen; Zeng, Shun-Xing; Li, Yue-Ping; Yang, Liu-Yun; Huang, Zi-Xuan; et al. (Frontiers in Neuroscience, 2022)
In response to external threatening signals, animals evolve a series of defensive behaviors which depend on heightened arousal. It is supposed that arousal and defensive behaviors are coordinately regulated by some neurocircuits in the central nervous system. The ventral tegmental area (VTA) is a key structure located in the ventral midbrain of mice. Recently, the activity of VTA glutamatergic neurons is shown to be closely related to sleep-wake behaviors. However, the specific role of VTA glutamatergic neurons in sleep-wake regulation, associated physiological functions, and underlying neural circuits remain unclear. In the current study, combining optogenetic manipulation with synchronous polysomnographic recordings, we showed that selective activation of VTA glutamatergic neurons induced immediate transition from sleep to wakefulness, and obviously increased the amount of wakefulness. Furthermore, optogenetic activation of VTA glutamatergic neurons induces a series of context-dependent defensive behaviors, including burrowing, fleeing, avoidance and hiding. Finally, by viral-mediated anterograde activation, we found that the projections from the VTA to the central nucleus of the amygdala (CeA) mediated the wake- and defense-promoting effects of VTA glutamatergic neurons. Collectively, our results illustrate that the glutamatergic VTA is a key neural substrate regulating wakefulness and defensive behaviors, and controls these behaviors through its projection into the CeA. Our results raise the possibility that the over-excitation of the glutamatergic VTA-CeA pathway may be implicated in the clinical psychiatric diseases characterized by the exaggerated defensive response, such as autism spectrum disorders.